2014
DOI: 10.1128/jvi.02029-14
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Type 1 E1^E4 Protein Is a Potent Inhibitor of the Serine-Arginine (SR) Protein Kinase SRPK1 and Inhibits Phosphorylation of Host SR Proteins and of the Viral Transcription and Replication Regulator E2

Abstract: The serine-arginine-specific protein kinase SRPK1 is a common binding partner of the E1^E4 protein of diverse human papillomavirus types. We show here for the first time that the interaction between HPV1 E1^E4 and SRPK1 leads to potent inhibition of SRPK1 phosphorylation of host serine-arginine (SR) proteins that have critical roles in mRNA metabolism, including pre-mRNA processing, mRNA export, and translation. Furthermore, we show that SRPK1 phosphorylates serine residues of SR/RS dipeptides in the hinge reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 65 publications
(94 reference statements)
5
37
0
2
Order By: Relevance
“…Prescott et al have recently shown that SRPK1 can also phosphorylate HPV1 E2 in vitro, even though it only contains three SR/RS dipeptides [56]. Furthermore, the E1ˆE4 proteins of many HPVs bind SRPK1 and inhibit its ability to phosphorylate E2 [56]. In our study, the observed interaction of the different E2 proteins with SRPK1/2 correlates somewhat with the number of SR/RS dipeptides in the hinge region (HPV8 has 28; others have 0 to 5).…”
Section: Factors Involved In Ptmsupporting
confidence: 58%
See 1 more Smart Citation
“…Prescott et al have recently shown that SRPK1 can also phosphorylate HPV1 E2 in vitro, even though it only contains three SR/RS dipeptides [56]. Furthermore, the E1ˆE4 proteins of many HPVs bind SRPK1 and inhibit its ability to phosphorylate E2 [56]. In our study, the observed interaction of the different E2 proteins with SRPK1/2 correlates somewhat with the number of SR/RS dipeptides in the hinge region (HPV8 has 28; others have 0 to 5).…”
Section: Factors Involved In Ptmsupporting
confidence: 58%
“…SRPK1 can phosphorylate the hinge region of HPV5 and HPV8 E2 proteins in vitro [6,55]. Prescott et al have recently shown that SRPK1 can also phosphorylate HPV1 E2 in vitro, even though it only contains three SR/RS dipeptides [56]. Furthermore, the E1ˆE4 proteins of many HPVs bind SRPK1 and inhibit its ability to phosphorylate E2 [56].…”
Section: Factors Involved In Ptmmentioning
confidence: 99%
“…SRPK1 and SRPK2 are cellular kinases that shuttle between the cytosol and nucleus and target proteins containing serine-arginine-rich domains (SR proteins) (for a review, see reference 34). It has been reported that SRPK1 also phosphorylates viral proteins (35)(36)(37)(38)(39). For example, SRPK1 is recruited by the E1^E4 proteins of human papillomaviruses and the ICP27 protein of herpes simplex virus 1, resulting in the downregulation of host SR protein phosphorylation (35,37).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that SRPK1 also phosphorylates viral proteins (34-38). For example, SRPK1 is recruited by the E1^E4 proteins of human papillomaviruses and ICP27 protein of herpes simplex virus 1, resulting in downregulation of host SR protein phosphorylation (34, 36). With regard to RNA viruses, inhibition of SRPK1 by SRPIN340 suppresses hepatitis C virus and human immunodeficiency virus replication, though these effects might be caused by modulation of RNA splicing through alteration of the SR protein phosphorylation status (24, 25).…”
Section: Discussionmentioning
confidence: 99%